Survey of olive agrosilvopastoral systems in Chalkidiki, N. Greece - Mantzanas K.; Papadimitriou M.; Sidiropoulou A.; Sklavou P.; Chouvardas D. (Pastoralism and sustainable development: proceedings, 2021)
Olive (Olea europea L.) is an important evergreen tree species of Mediterranean area that is planted in order to produce table olives and olive oil. Olive agrosilvopastoral systems are found in many regions of Greece; in combination with natural vegetation and/or intercropping. These systems are threatened by abandonment or conversion to intensive monocultures. The aim of this study was to identify olive agrosilvopastoral systems in the region of Chalkidiki, North (N) Greece and evaluate their characteristics. In order to achieve this, the Corine Land Cover classification system of land use types was applied on google earth satellite images and onsite observations were conducted. Three different systems were identified; a) silvoarable systems with trees in rows intercropped with cereals, b) silvoarable systems with scattered trees intercropped with cereals, and c) silvopastoral systems with scattered trees with natural vegetation and grazing. These systems were mainly found in the Corine land cover type 223 (olive groves) and occupied 12.052.64 ha of the study area. The majority of the systems were silvopastoral with scattered trees and natural vegetation. The preservation of the agroforestry systems of the area was mainly due to the occupation of the local population with tourism. The adoption of the new CAP agri-environmental measures by farmers could contribute further to their exploitation.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)